Region Community in Communication Theory - Murinska-Gaile, Sandra (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2014)
The aim of the report is to determine how local and regional newspapers represent local communities and how their communicative integration has been promoted. Mass media, establishing community cognition about its existence, involvement into the community, identification and belonging to the community, represent a perfect model of interaction between community and communication. During the content analysis of the press publications of local newspapers of Latgale region the typological characteristics and classification are emphasized, the role of the press in the development of the region inhabitants is defined, the direction and structure of the editorial board activities, newspapers’ content, authors and genres are inspected. The practice of local journalism varies in different places; there are some common trends but specific characteristics are noticed in each local community. They are being affected by social context, which is characterized by regional values and culture, since they correspond to the community and individual interaction as well. It is possible to see differences both in community structure, spread and in expressions of local newspapers within the region.